Peningkatan Hasil Belajar Matematika Materi Program Linier Melalui Penerapan Model Pembelajaran Discovery Learning Berbantuan Aplikasi Geogera Versi Android - Heri Risdianto Djumanan (Program Studi Matematika, Fakultas Teknik, Universitas Samudra. Langsa, Aceh., 2021)
The aimed of the research is to increasing students' understanding of the concept of the Linear Program, with the subject of research being the students of class XI IPA 2 of SMA Negeri 3 Langsa in the 2019/2020 Academic Year. The approach taken in this study is a qualitative approach using classroom action research design. The action is carried out in two cycles, the first cycle is the implementation of linear program learning material with the Guided Discovery Model assisted by Android Version of Geogebra software practiced by teacher, and the second cycle of implementing the Linear Program learning material with the Guided Discovery Model assisted by Android Version of the Geogebra software practiced by student. The data in this study were obtained by observation, questionnaires, and tests to the research object. Data obtained from observations and questionnaires were analyzed by means of qualitative analysis, while data obtained from tests were analyzed by quantitative analysis. The results showed that students' mastery of linear program material> 85% with an average final test result of 83.6.